Calcium/calmodulin‐dependent kinase II and memory destabilization: a new role in memory maintenance. Issue 1 (27th June 2018) - Vigil, Fabio Antonio; Giese, Karl Peter
Abstract: In this review, we discuss the poorly explored role of calcium/calmodulin‐dependent protein kinase II (CaMKII) in memory maintenance, and its influence on memory destabilization. After a brief review on CaMKII and memory destabilization, we present critical pieces of evidence suggesting that CaMKII activity increases retrieval‐induced memory destabilization. We then proceed to propose two potential molecular pathways to explain the association between CaMKII activation and increased memory destabilization. This review will pinpoint gaps in our knowledge and discuss some 'controversial' observations, establishing the basis for new experiments on the role of CaMKII in memory reconsolidation. The role of CaMKII in memory destabilization is of great clinical relevance. Still, because of the lack of scientific literature on the subject, more basic science research is necessary to pursue this pathway as a clinical tool. Abstract : Calcium/calmodulin‐dependent protein kinase II (CaMKII) is a kinase highly expressed at synapses in the brain. This enzyme has been shown to be necessary for memory formation, but its role on memory maintenance is still a matter of debate. Here, we discuss a new and unexplored role for CaMKII in memory maintenance. We present evidences indicating that after memory retrieval CaMKII is activated and contributes to memory destabilization. We propose two molecular pathways by which CaMKII may induce memory destabilization, involving protein degradation and/or increase in the synaptic levels of GluN2B. We also discuss the possibility that an endogenous CaMKII inhibitor protein controls retrieval‐induced memory destabilization.